Hydrocolpos with peritonitis in the newborn. Issue 7 (July 1980) - Gupta, I; Barson, A J
Abstract : Two cases of hydrocolpos are described presenting soon after birth. One infant who died on the first day had an intrauterine peritonitis caused by compression of the caecum on the pelvic brim. The other surviving infant developed a caecal perforation secondary to Hirschsprung's disease. Neither infant had rectal atresia, which is the commonest cause of intestinal obstruction in these infants. The association of hydrocolpos with polydactyly in one of these cases may represent an autosomal recessive trait.